Towards a Reconstruction of Enlightenment Values in a Changing World (Part one) - Abdellatif, Kamal (Münster journal for Islamic and philosophical studies, 2022)
‭ ‬In this study‭, ‬I consider that the Age of Enlightenment values are subjected to profound tests today in the context of its local and global history‭, ‬due to the general nature of its principles and to the similarity of human spiritual and civilized experiences‭, ‬in many of their manifestation‭. ‬That is why I emphasize in this study that the demand for enlightenment today is universal‭, ‬not the enlightenment of the eighteenth century‭, ‬but rather enlightenment as it developed in history‭, ‬with the need to distinguish between the nature of the demand in Arab societies and in Western societies‭. ‬In my view of the European Enlightenment Experience‭, ‬I do not stop at closed conceptions‭, ‬rather‭, ‬I accept a set of general historical theoretical principles‭, ‬which I consider as the organizing spirit of its philosophical choices‭. ‬I read the theoretical contribution of the Enlightenment in the context‭ ‬of modern philosophy and from an angle in which knowledge and political revolutions are assimilated‭, ‬as they have achieved and‭ ‬are being realized in modern and contemporary history‭, ‬whether in Europe or in other regions of the world‭. ‬It must be pointed out here‭, ‬that in this study I am concerned with the subject of the Enlightenment not as a moment in history‭; ‬my approach is to consider the Enlightenment as a critical theoretical activity that is still being established‭.‬